Socioeconomic Background as a Factor Contributing in Semilingualism - Sabir, Maryam; Bhatti, Zafar Iqbal (Pakistan Languages and Humanities Review, 2025)
This paper investigates the role of socioeconomic background as a significant contributing factor to the phenomenon of semilingualism, especially in underprivileged areas in Pakistan. Semilingualism describes an individual who has limited skills in multiple languages which yields inadequate communication with reduced cognitive growth. This study design involves the collection of qualitative data by conducting semi-structured interviews and direct observations with a total of 100 participants, including university and college students. Cummins’ threshold hypothesis together with critical capitalist perspectives to evaluate how social economic inequality affects bilingual and multilingual language development patterns through their analysis of gathered data. Research findings demonstrate that students from under privileged backgrounds face restricted language growth because they lack enough language exposure in their native tongue and their additional language. Moreover, this study explores the multifaceted relationships between economic status and linguistic progress while offering beneficial solutions to educational administrators who work to achieve linguistic justice and bilingual excellence among students from different backgrounds.